Neptune - Conrad, Michael W. (Dark Horse Comics, 2025)
"Haunted by his past, Corey Harrison finds himself finally freed from incarceration after serving 17 years for a violent crime. Now, Corey seeks the truth surrounding the recent and mysterious death of his brother, only to discover a vast darkness surrounding his legacy. Neptune is a bleak examination of the capitalist machine, and those trapped in its gears. At once violent and beautiful, grounded and hallucinatory; Michael Conrad (Tremor Dose, Double Walker, Wonder Woman, Batgirls) and breakout artist Nathan Ooten present a true tale of revenge and redemption."--